Distal tibial tuberosity translation using TTA implants for the treatment of patella alta in large breed dogs - Pugliese, L. C.; Pike, F. S.; Aiken, S. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Introduction: Medial patellar luxation frequently occurs in dogs resulting in lameness with increasing incidence in large breed dogs. Patella alta has been defined as a patellar ligament length to patellar length ratio that is greater than two and may predispose to patellar luxation.Objective: To describe the surgical technique for stabilization of the distal translation of the tibial tuberosity using tibial tuberosity advancement plates and the clinical outcomes with follow-up for clinical cases of dogs.Methods: Dogs that were presented with the complaint of patellar luxation and that were concurrently diagnosed with patella alta and were greater than 20 kg in body weight underwent surgery using a tibial tuberosity advancement plate to stabilize the osteotomy. Radiographic assessment of A:PL distance (the ratio of the proximal aspect of the patella to the femoral condyle [A] to the patellar length [PL]), L:P ratio (ratio of the length of the patellar ligament to the diagonal length of the patella), and owner assessment were obtained.Results: Eleven stifles in nine dogs underwent surgical correction with a mean preoperative L:P ratio of 2.47. There were no complications and the lameness resolved clinically. The mean A:PL ratios preoperatively (2.6 ± 0.22) and postoperatively (2.1 ± 0.25) were significantly different (p = 0.0003). All owners were satisfied with the outcome and all dogs had a resolution of lameness with no recurrence of patellar luxation.Clinical significance: Stabilization of distal translation of the tibial tuberosity using tibial tuberosity advancement implants to correct patella alta in large breed dogs was feasible and resulted in good clinical outcome.
Keywords: Patellar luxation; patella alta; tibial tuberosity advancement; TTA; large breed dogs